PERJUANGAN PEREMPUAN DAN NILAI MORAL DALAM NOVEL HIKAYAT ZAHRA KARYA HANAN AL-SHAYKY - Rifa Mazin Aqillah; Rohanda, Rohanda; Ainusyamsi, Fadlil Yani (Universitas Islam Malang, 2025)
The purpose of this article is to reveal the signs that exist in the novel in terms of moral values and the form of women's struggle according to the content of the story of a novel by Hanan Al-Shayky entitled Hikayat Zahra. In the story, Zahra represents a woman who lives under social and patriarchal pressures that limit her freedom. Through Zahra's journey, society can reflect on how rigid norms and patriarchy can harm individuals and the importance of a more inclusive, just and humane morality. The method used in this research is a descriptive qualitative method with the semiotic approach of Charles Sanders Peirce. From the signs that appear in the text, the researcher focuses on explaining the struggle of women and moral values. The results of the study show that there is a sharp and emotional narrative style, Hanan Al-Shaykh (the novelist) presents a critique of patriarchy and violence, and describes how individuals can be destroyed in an oppressive environment. By describing morality and the form of women's struggle, it is hoped that readers can understand that morality is not something static, but something that develops according to the existing social and cultural situation.